A research on marketing strategies of Landbank of the Philippines Guimaras Unified Systems Project (USP) - Gonzales, Rene Chito J. (1998)
This research is entitled "marketing Strategies of Land Bank of the Philippines Guimaras USP given its new site at San Miguel Jordan, Guimaras." It is intended to give answers to the following problem : "How will Land Bank of the Philippines Guimaras USPin Barangay San Miguel, Jordan promotes its existence to its prospective clients in the Province of Guimaras?" This problem is stated in the following objectives: 1. To come up with a socio-economic profile of depositors at the previous and current site; 2. To find out how the different products/services of Land bank fared with its depositors (old site and new site); 3. To assess the effectiveness of the promotionaltools used by the bank to its former and current depositors; 4. To assess factors that led depositor to engage their banking services with Land Bank; 5. To assess the degree of satisfaction of Land bank's services. To realize the above-listed objectives, the researcher used questionnaires and conducted interviews. The results are the following: 1. Both old site and new site depositor-respondents are young : teachers, farmers and cooperative staff by occupation, educated mostly in high school and college level; live in semi-strong houses; can afford to pay for electricity for their house lighting; own television and radio sets; but most of them don't have vehicles; 2. Banking services of LBP is considered Very Good as perceived by the respondents, consequently inviting future depositors. 3. Accessibility to residence of depositors is rated Very Good, a positive factor for customer retention and also an inviting factor for future depositors. 4. Television, radio and word of mouth are modes of promoting awareness of depositor; 5. All old and new site depositor-respondents alike are satisfied with the banks services. Most reasoned out fast service. Recommendations are follows: Intensify promotional efforts using broadcast media in their information drive to include television spots ; enlistment in the Philippine directory ; use advertising, public relations and sales promotions to communicate heir services/products to would-be clients or to the public in general.
Research Paper (BM 299 - Research Methods in Business Management). -- [Iloilo City : UPV-CM], October, 1998.